2020
DOI: 10.1097/md.0000000000021947
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of different skin closure in total-knee arthroplasty: running subcuticular closure vs intermittent closure

Abstract: An intermittent closure with silk suture is routinely used for closing different surgical wounds. However, subcuticular closure with absorbable sutures has gained considerable attention due to convenience and better cosmetic appearance. To compare the clinical outcomes and risk of surgical-site infection of subcuticular and intermittent closure after total-knee arthroplasty (TKA), 106 patients that underwent TKA between January 2017 to June 2019 at the Department of Orthopedics in Xiangya Hospital o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…26 Although RSC has been shown to have superior wound perfusion and cosmesis across multiple surgical subspecialties, its effect on postoperative wound complications in orthopaedic surgery is scarce and conflicting. [13][14][15][16][17][18][19][20][21] A meta-analysis of 6 studies by Smith et al 4 found that the risk of postoperative wound complications was 3.8 times greater for patients who received staples compared with those who received sutures. A subsequent systematic review and meta-analysis of 12 studies by Krishnan et al 5 found no differences in the rate of wound complications between these groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Although RSC has been shown to have superior wound perfusion and cosmesis across multiple surgical subspecialties, its effect on postoperative wound complications in orthopaedic surgery is scarce and conflicting. [13][14][15][16][17][18][19][20][21] A meta-analysis of 6 studies by Smith et al 4 found that the risk of postoperative wound complications was 3.8 times greater for patients who received staples compared with those who received sutures. A subsequent systematic review and meta-analysis of 12 studies by Krishnan et al 5 found no differences in the rate of wound complications between these groups.…”
Section: Discussionmentioning
confidence: 99%
“…4–14 More recently, studies in multiple surgical subspecialities have demonstrated that running subcuticular closures (RSC) result in improved wound perfusion and cosmesis when compared with staples or cutaneous mattress suture closures (CMC). 15–21 However, the use of RSC in orthopaedic trauma remains poorly studied and rarely used because of concern for increased risk of wound complications. 1,9,11,13,22…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the articular capsule, subcutaneous and skin layers were sequentially closed with one absorbable line (PDP359 and VCP359), a 2-0 VCP317 suture and a 3-0 VCP316 suture, respectively. Compared with intermittent closure, running subcuticular closure after TKA results in a better appearance [ 9 ]. All kinds of surgical and invasive procedures can induce epidermal inclusion cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Erythrocyte sedimentation rate (ESR) test is an inexpensive evaluation performed by measuring the distance that red blood cells (RBC) descend in a test tube (Westergren tube) within 1 h. A high ESR is found in inflammatory conditions due to a large increase in fibrinogen levels; it is usually used as a generic index of illness and for tracking inflammation in humans. ESR can be used to identify various diseases and conditions, such as acute tissue injury, infection, malignancy, rheumatoid arthritis, lymphoma, coronary disease, stroke, and heart failure, as well as for Available at www.veterinaryworld.org/Vol.14/September-2021/5.pdf postoperative monitoring [13][14][15][16][17]. ESR has rarely been analyzed in dogs, but it has been found to be useful in cases of canine rheumatoid arthritis, osteoarthritis, and babesiosis [18][19][20].…”
Section: Introductionmentioning
confidence: 99%